2018
DOI: 10.1111/acel.12746
|View full text |Cite
|
Sign up to set email alerts
|

The effects of graded caloric restriction: XII. Comparison of mouse to human impact on cellular senescence in the colon

Abstract: SummaryCalorie restriction (CR) is an effective strategy to delay the onset and progression of aging phenotypes in a variety of organisms. Several molecular players are involved in the anti‐aging effects of CR, but mechanisms of regulation are poorly understood. Cellular senescence—a cellular state of irreversible growth arrest—is considered a basic mechanism of aging. Senescent cells accumulate with age and promote a number of age‐related pathologies. Whether environmental conditions such as diet affect the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(36 citation statements)
references
References 20 publications
2
34
0
Order By: Relevance
“…Within the first group, studies in mice have shown that a 3-month, 26% calorically restricted diet started at adulthood can reduce the number of senescent cells in rapidly proliferating (intestinal) and slowly proliferating (hepatic) tissues [104]. A study of the human colonic mucosa showed that adults who had been voluntarily exposed to a 30% caloric restriction (with appropriate nutrition) for over 10 years had significantly reduced expression of p16 INK4a and reduced local concentrations of IL-6 [105]. A recent study in mice demonstrated that calorie restriction, even if started at adulthood, prevents fat deposition and the concomitant increase in telomere-associated DNA damage foci (TAF) in hepatocytes [106].…”
Section: How Can We Fight Cellular Senescence?mentioning
confidence: 99%
“…Within the first group, studies in mice have shown that a 3-month, 26% calorically restricted diet started at adulthood can reduce the number of senescent cells in rapidly proliferating (intestinal) and slowly proliferating (hepatic) tissues [104]. A study of the human colonic mucosa showed that adults who had been voluntarily exposed to a 30% caloric restriction (with appropriate nutrition) for over 10 years had significantly reduced expression of p16 INK4a and reduced local concentrations of IL-6 [105]. A recent study in mice demonstrated that calorie restriction, even if started at adulthood, prevents fat deposition and the concomitant increase in telomere-associated DNA damage foci (TAF) in hepatocytes [106].…”
Section: How Can We Fight Cellular Senescence?mentioning
confidence: 99%
“…Different studies have shown that CR reduce senescence markers in different mouse organs and human colon mucosa 9,[63][64][65][66] . One of the main inducers of senescence is cellular damage.…”
Section: Cr and Cellular Senescencementioning
confidence: 99%
“…[ 98 , 99 ]), and has also been demonstrated to substantially improve proteostasis in aged nematodes [ 7 , 109 , 110 ]. In humans, caloric restriction was shown to improve proteostasis [ 111 ] and reduce markers of senescence [ 112 ]. Interestingly, specific dietary supplements have been shown to improve the proteostasis capacity in aged nematodes, including oleic acid [ 113 ] and arachidonic acid [ 110 ], which was found to modulate HSF1 function [ 114 ].…”
Section: Modulation Of Proteostasis To Improve Aging Healthmentioning
confidence: 99%